2022
DOI: 10.3389/fnut.2022.796601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Composition During Neoadjuvant Chemoradiotherapy on Complications, Survival and Tumor Response in Patients With Locally Advanced Rectal Cancer

Abstract: BackgroundTo explore the impact of body composition before neoadjuvant chemoradiotherapy (pre-NCRT) and after neoadjuvant chemoradiotherapy (post-NCRT) on complications, survival, and tumor response in patients with locally advanced rectal cancer (LARC).MethodsPatients with LARC who underwent radical surgery after NCRT between Ja 22nuary 2012 and March 2019 were studied. Body composition parameters, including skeletal muscle area (SMA), muscle density (MD), visceral fat area (VFA), total abdominal fat area (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Starting from these results, a plan of action could be represented by the routinary analysis of body composition using the CT scan images. A correlation between low MD and postoperative complications in LARC patients was observed by Liu and colleagues, finding a correlation between MD and short-term and long-term ileus [36] . Also, Pekarova et al identified a correlation between low psoas density and worse postoperative complications [37] .…”
Section: Discussionmentioning
confidence: 58%
“…Starting from these results, a plan of action could be represented by the routinary analysis of body composition using the CT scan images. A correlation between low MD and postoperative complications in LARC patients was observed by Liu and colleagues, finding a correlation between MD and short-term and long-term ileus [36] . Also, Pekarova et al identified a correlation between low psoas density and worse postoperative complications [37] .…”
Section: Discussionmentioning
confidence: 58%
“…There were 278 potentially eligible publications on post‐diagnosis adiposity and colorectal cancer outcomes. We excluded 193 publications 45–237 due to specific reasons related to the synthesis (Supplementary Table 5). Finally, 85 publications…”
Section: Resultsmentioning
confidence: 99%
“…Body composition measurements, in particular SM surface area, have been associated with rectal cancer response to neoadjuvant therapy and corresponding survival outcomes [ 23 , 24 ]. Furthermore, body composition has been suggested as a superior method of dosing chemotherapy for CRC, to decrease rates of dose-limiting toxicity [ 8 , 25 ].…”
Section: Discussionmentioning
confidence: 99%